Phenolic composition, antioxidant and antibacterial properties, and in vitro anti-HepG2 cell activities of wild apricot (Armeniaca Sibirica L. Lam) kernel skins. (July 2019) - Qin, Fangling; Yao, Lu; Lu, Cairui; Li, Cong; Zhou, Yanyan; Su, Chencan; Chen, Bang; Shen, Yehua
Abstract: The polyphenols profiles of the methanol extracts of bitter apricot [ Armeniaca Sibirica (L.)] kernel skins (AKS) were analysed by liquid chromatography-electrospray ionization mass spectrometry. The antioxidan, anticancer effect on HepG2 cell and antibacterial properties of the AKS polyphenol extracts were further characterized in vitro . Polyphenol compounds (35), including nine phenolic acids, thirteen anthocyanins and thirteen flavonoids, were identified in AKS for the first time. The content of apigenin 7- O -glucoside, (cyanidin 3-(4″-acetylrutinoside), 3- (6″-acetylglucoside)-5-glucoside and salicylic acid was relatively high than the others. The AKS polyphenols strongly reduced Fe 3+ and exhibited good scavenging activity towards 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) free radicals, 1, 1-diphenyl-1-picrylhydrazyl free radicals, hydroxyl radicals, superoxide anions and hydrogen peroxide. The AKS polyphenols could regulate oxidant stress in HepG2 cells by downregulating reduced glutathione, upregulating oxidative glutathione, malondialdehyde and advanced oxidation protein products, and reduced cell viability to induce apoptosis of HepG2 cells in vitro . The AKS polyphenols showed strong antibacterial activity against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Acetobacter aceti and Bacillus cereus . Therefore, the antioxidant, inhibitory effect on HepG2 cells and antimicrobial activity of the AKS polyphenols were distinct and worthy of further consideration for medical industry applications. Highlights: Apigenin 7- O -glucoside was most abundant compound in the polyphenols from apricot ( Armeniaca Sibirica L. Lam) kernel skins. The polyphenols exhibited strong antioxidant activity towards free radicals and hydrogen peroxide (H2 O2 ). Polyphenols showed antibacterial activity against Escherichia coli, Staphylococcus aureus, Bacillus sp. The polyphenols had a significant inhibitory effect on the proliferation of HepG2 cells, while caused its apoptosis.